Digital Approaches to Public Relations by NGOS OF SA: A Qualitative Examination - Nchabeleng, G.; Botha, CJ; Bisschoff, CA (New Advances in Business, Management and Economics Vol. 5, 2025)
Global interconnectivity has rapidly increased following the rise and spread of social media. Social networking sites, blogging, email, instant messaging, and online journals are some of the technological changes that transformed the way interaction between people and how they gather information. Although social media is mainly used for interactive dialogue and social interaction, the private sector soon realized that web-based technologies (especially Facebook and Twitter) could also be a competitive business tool. Non-governmental organizations (NGOs) soon followed suit however at a slower pace than the general communication growth rate of social media in South Africa. For the foreseeable future, social media is here to stay and it will continue to evolve and grow in unprecedented ways. NGO business needs to create and maintain a social media presence and increase their brand awareness and return on investment, public relations practitioners. This article examines if social networking sites have any impact on the public relations practices of NGOs in South Africa – an environment where both customers and employees still struggle to take full advantage of social media. The critical literature findings increase the understanding of the current and future challenges of social media use in public relations at NGOs in South Africa. The study explores the main differences between traditional and social media, how social media is redefining the public relations role and sheds some light on defining public relations practices, identifying the uses, limitations and benefits of social media by public relations practitioners in NGOs. Recommendations for future communication research are given. Based on the literature, a qualitative research design collected data using semi-structured, individual interviews. The systemic grounded theory was used to determine a general explanation of the procedures and interaction among people. The results revealed that social media platforms such as Facebook do have an effect, and even changed the way in which NGOs communicate. The study also revealed that social media certainly has an impact on public relations relationships. This means that it has become crucial that public relations practitioners at NGOs embrace and take advantage of social media, and that they should also invest in proper electronic platforms to reap the benefits of improved communication internally and externally. The necessary support system for the NGOs should be designed, developed and sustained by the government. Further research in this area of social media would allow a complete understanding of new users’ experiences and would be particularly useful to practitioners who work in NGOs in understanding how to connect and inform stakeholders in social networks.